Establishing trends based on solvent system changes in cocrystals containing pyrogallol[4]arenes and fluorescent probes rhodamine B and pyronin Y1. Issue 24 (28th June 2015) - Pfeiffer, Constance R.; Fowler, Drew A.; Atwood, Jerry L.
<x xml:space="preserve">Abstract</x> Eight cocrystal structures containing a pyrogallol[4]arene of varying aliphatic tail lengths and either fluorescent probes rhodamine B or pyronin Y in a range of solvent systems are examined. Trends based on probe, solvent, and aliphatic tail length are investigated.